ANALYSIS OF SHOCK ABSORBERS STRUCTURES OF LONGITUDINAL TORSIONAL VIBRATIONS OF THE DRILLING COLUMNS - Moisyshyn, V. М.; Vekeryk, V. I. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2024)
Anti-vibration devices should be considered one of the most rational ways to improve the working conditions of the rock-destructive tool, and therefore, the drilling performance. The energy of longitudinal and torsional vibrations is transformed into the potential energy of compression deformation and torsion of the elastic elements of shock absorbers. Designs of shock absorbers of longitudinal torsional vibrations of the drill string are considered. According to the design and material of the node that perceives the vibrations of the drill string, devices are distinguished: with metal elastic elements, with rubber elements, and with rubber-metal elements. The main parameters of the shock absorbers include the axial and torsional stiffness coefficients and damping of the elastic element of the unit, which perceives the vibrations of the drill string. The design features of fifteen devices, which reduce the level of vibration of the rock-destructive tool, are analysed, and the comparative characteristics of their elastic elements are given.